Bluntness in Popular Culture: The Trump Era’s Ascent - Banu, Sultana; Sharma, Balkrishna; Pokharel, Bishnu Prasad (BMC Research Journal, 2025)
This research examines the mainstream media to illustrate their substantial influence in elevating Donald Trump as a presidential candidate during the 2016 US election. His confrontations with rival parties, distinctive rhetoric, and choice of language garnered significant attention. His language, reactions, and remarks regarding Hillary Clinton, media representatives, and women reflect fundamentalist ideologies that are pertinent to critical discourse analysis, emphasizing the role of discourse as a form of social interaction. Halliday’s Language as Social Semiotics, Michel Foucault’s concept of the Technology of Self, Karl Marx’s Dialectical Materialism as analytical frameworks to justify the argument. This study employs these critical discourses as a theoretical framework to analyze Donald Trump’s auditory, visual, printed, and multimodal communication. The main media purposively sampled for analysis are the BBC, CNN, The New York Times, The Guardian, and Fox News. Consequently, he emerged victorious in the election, serving as the President of the United States from 2017 to 2021. To analyze the argument that these selected media outlets framed Trump as a central figure during the 2016 election in America. The findings indicate that blunt media discourse contributed to maintaining his image as a national business magnate, amplified by prominent media outlets. Ultimately, the paper highlights how Trump's statements and media responses generated compelling news coverage, significantly contributing to his global recognition.